Macroeconomic Effects of Reallocation Shocks: A Generalised Impulse Reponse Function Analysis for Three European Countries - Theodore Panagiotidis; Gianluigi Pelloni; Wolfgang Polasek (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2003)
We develop a generalised impulse response function (GIRF) approach to explore the different impacts of aggregate and sectoral shocks within a VAR-GARCH-M model. Using the output of our GIRF analysis, we explore the behaviour of three European countries (Germany, Spain and the UK). We analyse the aggregate and sectoral responses to discriminate among three different hypotheses of business cycle fluctuations. Links are established and explanations are provided within the still experimental character of our exercise.
Keywords: 330; Konjunktur; Schock; Allokationseffizienz; Strukturwandel; ARCH-Modell; Deutschland; Spanien; Großbritannien; Wirkungsanalyse